2019
DOI: 10.1159/000500853
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Impacts on Cardiac Mortality in Nepali Migrant Workers in Qatar

Abstract: Background: Qatar is a major destination country for Nepali migrant workers (NMWs; main age range 25–35 years) in the construction trade. These 120,000+ NMWs are exposed to various occupational hazards, including excessive heat, and 3–4 workers die each week. Our study aimed to show whether heat exposure caused deaths. Methods: The worker population and mortality data of NMWs were retrieved from government institutions in Nepal. Heat exposure was assessed by monthly estimates of daily wet bulb globe temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…Furthermore, a higher risk of mental health problems [9,13], acute and chronic pesticide poisoning [9,18] and heat-related illness [5,7,[19][20][21][22] were reported among migrant and seasonal farm workers. However, underreporting of medical conditions is significant due to limited access to health services, and fear of lost wages or jobs [23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a higher risk of mental health problems [9,13], acute and chronic pesticide poisoning [9,18] and heat-related illness [5,7,[19][20][21][22] were reported among migrant and seasonal farm workers. However, underreporting of medical conditions is significant due to limited access to health services, and fear of lost wages or jobs [23].…”
Section: Introductionmentioning
confidence: 99%
“… 19 Third study looked at the chronic kidney disease among workers and found that 13.6% of workers had diabetic nephropathy. 37 In the study by Pradhan et al, 35 cardiovascular disease, natural/others reasons and murder contributed to 42%, 25% and 1.7% of deaths, respectively. The last study reported that of patients attending to the emergency medical service in Qatar, out-of-hospital cardiac arrest among Nepalese migrant patients was found to be 11.6% 22 ( table 1 ).…”
Section: Resultsmentioning
confidence: 95%
“… 39 Another study reported that more than one-quarter (25.4%) of migrants had traffic related pedestrian injuries during abroad work 20 ( table 1 ). A study by Pradhan et al 35 conducted a retrospective analysis of Government of Nepal data from 2009–2017 and recorded 1345 deaths, of which workplace accident and road traffic accidents contributed to 12% and 10% deaths, respectively. 33 cases of work-related ocular injuries were reported in one study among Nepalese patients of the 440 patients attending a hospital in Malaysia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations